Idioms of resilience among cancer patients in urban South Africa: An anthropological heuristic for the study of culture and resilience - Kim, Andrew Wooyoung (Transcult Psychiatry, 2019)
Despite the large body of research on idioms of distress in anthropology and transcultural psychiatry, few scholars have examined the concepts that people use to describe social and psychological resilience. The experience of social and psychological resilience is embedded in and shaped by social, political, and economic contexts—much like the factors that shape idioms of distress. As resilience literature more broadly has adopted a socio-ecological rather than trait-based approach, anthropology has much to contribute. This article investigates what idioms of resilience and cultural scripts emerge among low-income patients with cancer residing in Soweto, a peri-urban neighborhood in Johannesburg, South Africa. We conducted 80 life history interviews to better understand what social and psychological factors led some people to thrive more than others despite extraordinary adversity. We describe one idiom of resilience, acceptance (ukwamukela in isiZulu), and three broader themes of resilience that emerged from life history narrative interviews (social support, religious support, and receiving medical care). We also present two examples from study participants that weave these concepts together. Our findings suggest that rarely is one form of resilience experienced in isolation. A focus on idioms of resilience can help chart the complex dimensions of acceptance and the dynamic social, religious, political, and temporal factors that mediate both suffering and resilience within individuals and communities.